Resistance in Soybean Against Infection by Phakopsora pachyrhizi Is Induced by a Phosphite of Nickel and Potassium - Bianca Apolônio Fontes; Leandro Castro Silva; Bárbara Bezerra Menezes Picanço; Aline Vieira Barros; Isabela Maria Grossi Leal; Leonardo Packer Quadros; Fabrício Ávila Rodrigues (Plants)
Soybean (Glycine max (L.) Merr.) is one of the most profitable crops among the legumes grown worldwide. The occurrence of rust epidemics, caused by Phakopsora pachyrhizi, has greatly contributed to yield losses and an abusive use of fungicides. Within this context, this study investigated the potential of using a phosphite of nickel (Ni) and potassium (K) [referred to as induced resistance (IR) stimulus] to induce soybean resistance against infection by P. pachyrhizi. Plants were sprayed with water (control) or with IR stimulus and non-inoculated or inoculated with P. pachyrhizi. The germination of urediniospores was greatly reduced in vitro by 99% using IR stimulus rates ranging from 2 to 15 mL/L. Rust severity was significantly reduced from 68 to 78% from 7 to 15 days after inoculation (dai). The area under the disease progress curve significantly decreased by 74% for IR stimulus-sprayed plants compared to water-sprayed plants. For inoculated plants, foliar concentrations of K and Ni were significantly higher for IR stimulus treatment than for the control treatment. Infected and IR stimulus-sprayed plants had their photosynthetic apparatus (a great pool of photosynthetic pigments, and lower values for some chlorophyll a fluorescence parameters) preserved, associated with less cellular damage (lower concentrations of malondialdehyde, hydrogen peroxide, and anion superoxide) and a greater production of phenolics and lignin than plants from the control treatment. In response to infection by P. pachyrhizi, defense-related genes (PAL2.1, PAL3.1, CHIB1, LOX7, PR-1A, PR10, ICS1, ICS2, JAR, ETR1, ACS, ACO, and OPR3) were up-regulated from 7 to 15 dai for IR stimulus-sprayed plants in contrast to plants from the control treatment. Collectively, these findings provide a global picture of the enhanced capacity of IR stimulus-sprayed plants to efficiently cope with fungal infection at both biochemical and physiological levels. The direct effect of this IR stimulus against urediniospores’ germination over the leaf surface needs to be considered with the aim of reducing rust severity.